The Effectiveness of the Use of Three-Dimensional Media in IPAS on Student Learning Outcomes at Madrasah Ibtidaiyah - Martanti, Fitria; Baihaqi, Muhammad Imam; Farda, Ummu Jauharin (At-tadzkir: Islamic Education Journal, 2025)
This study aims to determine the effectiveness of using three-dimensional mockup media in social studies learning for fifth-grade students at MI NU 13 Gebanganom Wetan Kendal in the 2024/2025 academic year. The method used was quantitative, with an experimental approach and a one-group pretest-posttest design. The study population comprised all fifth graders, using a total sampling technique. Data is collected through pretest and posttest tests, observation, and documentation. Data analysis included normality, homogeneity, t-test (Paired Sample Test), and the normalized N-Gain test. The results showed a significant increase in student learning outcomes, with an average pretest score of 55.39 increasing to 82.50 in the posttest. The lowest and highest scores also increased significantly. The t-test showed a significant difference (p = 0.000 < 0.05) between the pretest and the posttest. At the same time, an average N-Gain of 0.63947 (63.95%) indicates that the mockup media is highly effective. This study recommends developing mockup media using digital technology, testing at the classroom level, and using other materials to expand applications and improve the quality of learning in the technological age.